(untitled) (Balthazar, 2024)
The idea of convenientia was already conceptualised and exploited as a key notion in aesthetic reflection in classical Latin culture. But the term also belongs to other lexical domains, notably that of ethics, in which it has been originally adopted to indicate the form of a duty in relation to an order that transcends the subject. In this article, we explore the vicissitudes of this notion in French philosophy at a crucial linguistic and cultural turning point, the seventeenth century, when Latin was dethroned by the vernacular languages. Against this background of instability in the philosophical lexicon, we will focus on two authors who recovered and “adapted” the Latin concept of convenientia, contributing to redefine its meaning and value as convenance in French-language philosophy: Pierre-Sylvain Régis (1632-1707) and Nicolas Malebranche (1638-1715). The adoption of a comparative approach between these two authors, who were almost perfect contemporaries and whose works stand in the same Cartesian tradition, has a double advantage: it allows to grasp the particularity of the interpretations of the two authors while offering a “sample” that testifies to the echo and the role assigned to the notion of convenance in French philosophy at the end of the seventeenth century. The result of the reworking of this concept, particularly by Régis, leads to a rapprochement between the “ethical” and “aesthetic” meanings of convenance.